Evaluasi Penerapan Sistem Budidaya Padi Organik di Kecamatan Petarukan, Kabupaten Pemalang - Fauzi, Ahmad; Ahadiyat, Yugi R (Biofarm : Jurnal Ilmiah Pertanian, 2023)
The organic agriculture system is a sustainable farming practice that has a promising solution for the sake of both food and the environment. Nevertheless, the adoption of organic systems in rice cultivation has been slowly developing due to some constraints for the lower yield than that of conventional systems. Rice production in the Pemalang region has mainly been cultivated in the district of Petarukan where some farmer grows in an organic system. This study was conducted to compare soil chemical properties i.e. pH, C-organic, N, P, and K in organic, conventional, and conversion systems of rice cultivation. In addition to the survey for collecting soil samples, the history of land management was investigated through farmer interviews. Soil samples were collected from each management type in 5 different locations using the composite sampling technique. The observed soil chemical parameters were statistically analyzed using one-way ANOVA and Tukey-test for further comparison. The result shows that the C-organic, pH, and N-total of three different cultivation systems were not different. On the other side, there was a difference among cultivation systems in P and K of the soil. This result indicates that there is a gap to fill to improve organic rice yield through enhancing soil organic matter.